Chants, Raps and Songs - How they enhance language learning - Fernandes, Paula Cristina de Mira (2020)
This action research study aims to show how chants, raps and songs can enhance language memorisation in an English as a Foreign Language classroom and what contributes to it. During my second practicum period I collected data through questionnaires, worksheets, observation grids, a learning journal and students’ interviews. These tools helped me understand what is behind chants, raps and songs when teaching a foreign language. I learned that my students loved rhythm, rhymes, repetition, gestures, imitation, body language, intonation and that all of these combined were a booster to language memorisation. I observed that there was language appropriation and that children were able to recall chants, raps and songs taught in the class through repetition, gestures and rhythm. Chants, raps and songs also contributed to “maximise language pronunciation, intonation, ear training…” (Brewster, Ellis & Gerard, 2002, p.164). They have beats that contribute to language learning through the repetition of chunks, enhancing memory ability. Teachers may use chants, raps and songs as “warmers, as closers, to introduce new language, to practise language, to revise language (Brewster, Ellis & Gerard, 2002, p.168). Should teachers use these more often they may contribute to the ability to train their students’ memory.